A combined MaxEnt and GIS‐based methodology to estimate cactus pear biomass distribution: application to an area of southern Italy. (27th October 2021) - Leanza, Paola Maria; Valenti, Francesca; D'Urso, Provvidenza Rita; Arcidiacono, Claudia
Abstract: The need to investigate suitable alternatives to conventional fossil fuels has increased interest in several renewable energy sources, especially in widely available sources of biomass. This has made environmental and socio‐economic improvements possible. In recent years, biogas from biomass has increasingly been considered the most feasible alternative to energy from fossil fuel, as it allows both the possibility to reduce waste disposal treatment and the opportunity to produce green energy. Opuntia ficus‐indica (OFI) has been suggested as a possible biomass as it could represent a suitable resource for producing biomethane as a new frontier within the context of a circular economy. This study aims to define a methodology for evaluating the distribution of OFI biomass that is potentially available for biogas production by applying maximum entropy modeling in a case study of a province located in southern Italy. The geographic information system (GIS)‐based model that was developed made it possible to estimate the suitability of the species in the territory and to define specific indices at the municipal level by enabling the localization of the highest productive territorial areas. Municipalities were grouped into three different classes ranging from low to high potential ones. In future years, new municipalities could be part of the high‐potential group, due to global warming resulting from climate change. The results could be relevant to the intervention priorities established by the European Union related to the planning activities supported by the European Structural and Investment Funds within the Smart Specialization Strategy. In this regard, knowledge of the potential production and distribution of a species in a territory is highly valuable information for the quantification of the biomass potentially available for biogas production, prior to strategic planning for the improvement of the biogas sector. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd